Efficacy of Escitalopram (SSRI) for Better Glycemic Control in the Diabetic Depressive Patients - Israt, Ummey Honey; Iqbal, Md Jalal Uddin; Rowshan, Mahfuza Mazeda; Sultana, Sadia; Ahmed, Shehreen; Sultana, Nadia; Badrudozza, ASM (Sir Salimullah Medical College Journal, 2022)
Background: Diabetes Mellitus is one of the most common disease in the world. Depression is most common among Diabetic patients, that causes morbidity and mortality. For prevention, we need to anti depressive agents with continued treatment for better compliance. So, it is important evaluate the efficacy of Escitalopram (SSRI) for better glycemic control in Diabetic Depressive patients. Objective: To assess the effect of Escitalopram (SSRI) on glycemic control in Type-2 Diabetic Depressive patients. Methods and Materials: A prospective observational study was done in Sir Salimullah Medical College and Mitford Hospital and BIRDEM General Hospital from January 2018 to December 2018.A total number of 35 diabetic and newly diagnosed depressive patients were taken and given tab. Escitalopram with continued diabetic treatment. Here, pre and post baseline investigations (FBG, Post prandial blood glucose and HbA1c levels) measured on day 1 , follow up at 6 weeks,12 weeks and then compared. Results: Patients treated with Escitalopram, pretreatment shows mean base line FBG 10.41 ±1.84mmol/L which was reduced to 8.56±1.55 mmol/L at 6 weeks and 7.51±1.26mmol/ L on 12 weeks. Similarly baseline mean 2HABF (post prandial) blood glucose 14.16±2.48mmol/L which was reduced to 12.41.01±2.34 mmol/L on 6 weeks and 10.96±1.75 mmol/L in 12 weeks .Mean baseline HbA1c 8.88±0.67% after in 12 weeks it was reduced to 7.82±0.98% . Here significant changed in blood glucose and HbA1c levels compared to pretreatment with Escitalopram (Treatment glucose and HbA1c levels compared to pretreatment with Escitalopram & only anti diabetic drugs. Conclusion: Escitalopram has better efficacy on glycemic control in Diabetic Depressive patients than patients treated with antidiabetic alone. Sir Salimullah Med Coll J 2021; 29(2): 100-104